The San Antonio Conference: Some Orthodox Reflections - Lemopoulos, George (International review of mission, 1990)
The author of this article is very grateful to all Orthodox participants in the San Antonio conference, the feelings of which he attempts to reflect here. In particular, he would like to thank Fr Alexander Veronis and Fr Cyrill Argentis who kindly shared their reflections (on which this article is based) with CWME staff.